Reliable steganalysis of color images based on color gradient sequence - QI Ke1; ZHANG Da-fang1; XIE Dong-qing2 (Tongxin xuebao)
Based on the difference between the vibrations of color gradient orientation sequences and color gradient sum sequences of stego images and those of images without hiding message,a novel reliable steganalysis of color images was presented which major in the analysis of these two categories of color gradient sequences,which could distill the differ-ences of the vibrations of them.The Hilbert-Huang transform based characteristic vectors were constructed and the SVM classifier was used to classification.The experimental results have shown that the proposed method realizes the reliable steganalysis of color images with higher correct rate,shorter vectors and lower false positive rate comparing with tradi-tional color image steganalysis algorithms.